Failure Factors of Early-Stage Digital Startups: A Literature Review: Failure Factors of Early-Stage Digital Startups: A Literature Review - Fadillah, Bagus (International Conference on Digital Business Innovation and Technology Management (ICONBIT), 2025)
Digital startups are increasingly shaping the modern economy, yet a high failure rate in early-stage ventures remains a critical concern. This study investigates the underlying causes of early-stage digital startup failure through a Systematic Literature Review (SLR). Focusing on publications from 2017 to 2025 indexed in the Scopus database, we applied the search string “failure startup” OR “regression startup” AND “technology” and identified 13 relevant studies. The review reveals that failure is influenced by internal factors—such as weak managerial competence, misaligned business strategies, and team conflicts—and external factors including market volatility, lack of ecosystem support, and rapid technological shifts. The study also highlights the concept of “regression startup,” where decline results from a series of poor strategic decisions. A combination of lean startup approaches, entrepreneurial training, and policy- level innovation interventions is recommended to mitigate risks. This review offers a conceptual contribution to understanding early-stage digital startup failure in a technology-driven context and emphasizes the need for more resilient strategic planning.